MENSAJE INDÍGENA ANDINO SUBYACENTE EN LA PINTURA DE ANTONIO HUILLCA HUALLPA: UTOPÍAS FILOSÓFICAS Y COSMOVISIÓN - CÁCERES-CHALCO, Efraín (2024)
The objective was to analyze the Andean communication system through Huilca’s painting, whose production integrates messages, symbols,categories and codes that express the experiences, logic and culture of the Andean indigenous communities. The work methodology: the research is basic, explanatory level, with a qualitative approach, through in-depth interviews, testimonies, life stories of the key informant, the research is developed considering the Interpretative Hermeneutic Paradigm; To analyze the underlying messages in the pictographic medium, the Semiotic-Structural Method of the French School has been used. The results allow us to conclude that painting is a means of communication with symbolic messages, which to this day are valid, since they collect ways of life, with which the population fully identifies. The conclusions: the indigenous Andean pictographic universe manages a universe of colors that symbolize each of the messages of life and death, such as yellow and red, which express life, and black and brown, death; The graphic representations are broad, expressing the universe holistically, and not casuistically.